Stress susceptibility in Trypanosoma brucei lacking the RNA-binding protein ZC3H30. - Chaitali Chakraborty; Christine Clayton (Public Library of Science (PLoS), 2018)
Trypanosomes rely on post-transcriptional mechanisms and mRNA-binding proteins for control of gene expression. Trypanosoma brucei ZC3H30 is an mRNA-binding protein that is expressed in both the bloodstream form (which grows in mammals) and the procyclic form (which grows in the tsetse fly midgut). Attachment of ZC3H30 to an mRNA causes degradation of that mRNA. Cells lacking ZC3H30 showed no growth defect under normal culture conditions; but they were more susceptible than wild-type cells to heat shock, starvation, and treatment with DTT, arsenite or ethanol. Transcriptomes of procyclic-form trypanosomes lacking ZC3H30 were indistinguishable from those of cells in which ZC3H30 had been re-expressed, but un-stressed bloodstream forms lacking ZC3H30 had about 2-fold more HSP70 mRNA. Results from pull-downs suggested that ZC3H30 mRNA binding may not be very specific. ZC3H30 was found in stress-induced granules and co-purified with another stress granule protein, Tb927.8.3820; but RNAi targeting Tb927.8.3820 did not affect either ZC3H30 granule association or stress resistance. The conservation of the ZC3H30 gene in both monogenetic and digenetic kinetoplastids, combined with the increased stress susceptibility of cells lacking it, suggests that ZC3H30 confers a selective advantage in the wild, where the parasites are subject to temperature fluctuations and immune attack in both the insect and mammalian hosts.